Chronic Hypertension and Pregnancy Outcomes: Systematic Review and Meta-Analysis. Issue 1 (March 2015) - Bramham, K.; Parnell, B.; Nelson-Piercy, C.; Seed, P.T.; Poston, L.; Chappell, L.C.
Abstract : ( BMJ . 2014;348:g2301)